INSTABILITY OF SOLITARY WAVE SOLUTIONS OF A CLASS OF NONLINEAR DISPERSIVE SYSTEMS (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
In this paper the orbital stability and instability properties of solitary wave solutions of a class of nonlinear dispersive systems are studied. By applying the abstract results of Grillakis et al. ([11]), we obtain the stability of the solitary waves.